Doing Church Diaconal Service in the Context of Ecological Crisis in Indonesia - Hehanussa, Jozef M. N. (Diaconia, 2024)
In Indonesia, diaconia is primarily associated with economic and social issues. Diaconal services predominantly aim to improve the community’s economy, but there are also charitable programs that help meet basic needs. However, there are only few diaconal programs focused on environmental or ecological issues, despite the serious environmental challenges Indonesia faces. Natural disasters such as floods, landslides, and waste-related problems highlight the urgent need for Indonesia to address ecological concerns. Therefore, the church’s diaconia must encompass ecological issues as well. By integrating environmental care into its ministries, the church can provide holistic support that preserves the integrity of creation. This paper explores the church’s perspective on ecology and its implications for ministry. Qualitative research methods were employed to collect data through interviews and questionnaires. These questionnaires were distributed to pastors and church activists to gather information about the church’s diaconal ministry, particularly regarding ecological issues. Based on the collected data, I examined the willingness of churches to take the initiative in developing diaconal ministries focused on environmental concerns. Churches in Indonesia recognize that participation in ecologically related diaconal ministries is essential to sustaining God’s creation for the future and thus their responsibility to address the ecological crisis through their ministries.